2016
DOI: 10.1113/jp273089
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular vascular and metabolic adaptations to high‐intensity interval and moderate intensity continuous training: a randomized trial in healthy middle‐aged men

Abstract: High-intensity interval training (HIIT) is a time-efficient way of obtaining the health benefits of exercise, although the cardiac effects of this training mode are incompletely known. We compared the effects of short-term HIIT and moderate intensity continuous training (MICT) interventions on myocardial perfusion and metabolism and cardiac function in healthy, sedentary, middle-aged men. Twenty-eight healthy, middle-aged men were randomized to either HIIT or MICT groups (n = 14 in both) and underwent six cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 53 publications
7
20
3
Order By: Relevance
“…Regardless of the development of new tracers, [ 18 F]FTHA is still widely used. At Turku PET Centre, we have used [ 18 F]FTHA in numerous studies of fatty acid metabolism in, for example, the myocardium, adipose tissue function, and obesity …”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the development of new tracers, [ 18 F]FTHA is still widely used. At Turku PET Centre, we have used [ 18 F]FTHA in numerous studies of fatty acid metabolism in, for example, the myocardium, adipose tissue function, and obesity …”
Section: Introductionmentioning
confidence: 99%
“…Given our findings are of a similar magnitude, even though total weekly duration is much lower, then this suggests that the duration of the sprint is not a driving factor in blood pressure adaptation to SIT. Ejection fraction does not appear to change with either endurance training [4] or with 30-s repeated high intensity bursts [29] and resting heart rate was unchanged in this study (data not reported). It could be speculated that improvements in pulse pressure at rest, reported in this study, reflect changes in arterial stiffness or wave reflection.…”
Section: Blood Pressure Changesmentioning
confidence: 46%
“…We have previously published several reports from this study (9,10,16,17,24,25,37). The main parameters of the present study, epi- and pericardial fat masses and MTC, have not been published before neither in healthy nor in DGT subjects.…”
Section: Methodsmentioning
confidence: 91%